Pengaruh siswa tipe introvert dan ekstrovert terhadap kesiapan belajar dan hasil belajar - sania, mas udatus (Maliki Interdisciplinary Journal, 2025)
This study examines the influence of introverted and extroverted personality characteristics on student readiness to learn and learning outcomes. It was found that introverted students tend to focus more on deep understanding but may have difficulty in social interaction, while extroverted students tend to be more active in communication but may be less focused on details. This can impact their academic performance, with extroverted students tending to have higher academic scores. Based on these findings, it is recommended that educators understand students’ individual needs, encourage collaboration between students, and provide appropriate support according to their personality characteristics. It is hoped that with this approach, students’ overall learning readiness and learning outcomes can be improved. Furthermore, this study highlights the importance of implementing adaptive learning strategies to address differences in student personality characteristics. In the context of modern learning increasingly influenced by digital technology, a blended learning approach can be an effective solution to accommodate the needs of students with various personality types. Through a combination of online and face-to-face learning, introverted students have the opportunity to learn independently and reflectively, while extroverted students can channel their need for social interaction through collaborative activities and group discussions. Thus, the learning process is not only more inclusive but also more effective in increasing student engagement and academic achievement. This research is expected to contribute to the development of more personalized and individual-oriented learning strategies in educational environments.